2011
DOI: 10.1097/nen.0b013e3182032d37
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis-1 Heterozygosity Increases Microglia in a Spatially and Temporally Restricted Pattern Relevant to Mouse Optic Glioma Formation and Growth

Abstract: While carcinogenesis requires the acquisition of driver mutations in progenitor cells, tumor growth and progression is heavily influenced by the local microenvironment. Previous studies from our laboratory have employed Neurofibromatosis-1 (NF1) genetically engineered mice to characterize the role of stromal cells and signals to optic glioma formation and growth. Previously, we have shown that Nf1+/- microglia in the tumor microenvironment are critical cellular determinants of optic glioma proliferation. To de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
105
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 58 publications
4
105
0
1
Order By: Relevance
“…More specifically, Ptprd +/− p16 −/− tumors had activated genes involved in up-regulation of several chemokines, all of which promote M2 polarization (23)(24)(25)(26). Macrophages can enhance tumor cell survival by promoting tumor growth, invasion, or immunosuppression (27)(28)(29)(38)(39)(40). In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Ptprd +/− p16 −/− tumors had activated genes involved in up-regulation of several chemokines, all of which promote M2 polarization (23)(24)(25)(26). Macrophages can enhance tumor cell survival by promoting tumor growth, invasion, or immunosuppression (27)(28)(29)(38)(39)(40). In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NF1 haploinsufficiency in the cellular environment of a tumor promotes its progression in vivo. That observation was made in Nf1 mouse models in both plexiform neurofibromas [Yang et al, 2008;Staser et al, 2012] and optic gliomas [Daginakatte and Gutmann, 2007;Simmons et al, 2011], e.g. via hyperactivated Nf1 +/-mast cells as critical mediators [Khalaf et al, 2007;Parrinello and Lloyd, 2009;Staser et al, 2010].…”
mentioning
confidence: 99%
“…3B), where 35%-55% of the cells in these PA tumors were microglia/macrophages. This level of stromal contamination with microglia/macrophages is similar to that observed in both sporadic low-grade and high-grade gliomas (Simmons et al 2011). Next, we evaluated that possibility of large-scale somatic rearrangements in other genes potentially cooperate with NF1 loss during PA formation or growth by performing copy number alteration analysis of WGS read data using the cnvHMM algorithm (Chen et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of these stromal cells to NF1 glioma growth is further supported by several studies using Nf1 GEM strains. In these experiments, pharmacologic or genetic silencing of microglia reduces glioma growth and proliferation Daginakatte et al 2008;Simmons et al 2011). The mechanism underlying their glioma-promoting properties has not been fully elucidated, but likely involves the generation of growth factors and chemokines Warrington et al 2007;Wesolowska et al 2008;Zhai et al 2011).…”
Section: Discussionmentioning
confidence: 99%